Islamic Symbolism in the Marriage Customs of the Mandailing People: A Study on Religious Meanings and Rituals - Novita Sari (Yayasan Bayt Shufiya Nusantara, 2024)
This research aims to explore Islamic symbolism in the practice of Mandailing traditional marriage. This study uses a qualitative method with a research location in Ampung Padang Village, Batang Natal District, Mandailing Natal Regency. Primary data were obtained through interviews with village heads, traditional leaders, religious leaders, bride and grooms, and local communities, while secondary data were obtained from relevant literature. The results of the study show that traditional symbols such as panaek gondang, gates, ulos, burangir, and upa-upa, reflect Islamic values such as sincerity, compassion, prayer, blessings, and social and spiritual ethics in married life. This symbolism shows the harmonization between customs and sharia, thus making Mandailing traditional marriage a space for integration between cultural values and Islamic teachings.